Active Ageing in the Nordic Countries: Introduction - Salomon, Robert H. (Nordic Journal of Working Life Studies, 2012)
The year 2012 is designated as the European Year for Active Ageing and Solidarity between Generations. The aim of the year is to raise awareness of the position of older people in a manner where they can enjoy a better quality of life and still play an active role in society. There are good reasons for designating 2012 as such a year. The OECD has estimated that by the year 2050, more than 33% of men and 38% of women in the EU25 will be 60 years or older compared with 18% and 24%, respectively, for the year 2000. The European Statistical Office projects that by 2060, there will be only two people of working age (15–64) in the EU for every person aged over 65, compared with a ratio of 4 to 1 today. Keeping in mind that an increasing share of the youth between 15 and 30 are studying, the consequences of these figures are even more challenging. Many politicians are seriously concerned about financing of the pensions and welfare systems. Another concern is how to allocate sufficient healthcare personnel to give the ageing population a decent service. These challenges are good reasons for the EU to include “solidarity between generations” as an element in the activity of this year. This special issue on active ageing is a contribution from the Nordic Journal of Working Life Studies to the year of active ageing. The articles examine work and ageing from different angles and horizons of understanding. Together, the articles question some of the myths that exist on ageing and work and assess some of the actions being taken to keep older workers in employment. This issue is therefore an important contribution to the development of our understanding of active ageing and measures used to develop an active ageing policy (...)